Connection between electrodes shape and plasma flow of the gliding discharge - Sláma, J.; Píchal, J. (Вопросы атомной науки и техники, 2011)
Contribution deals with form of electrodes and corresponding shape of plasma flow in the gliding discharge
reactor. Gliding discharge sustained in air at atmospheric pressure and room temperature. There were studied three
elemental electrodes configuration. Plasma was investigated by means of its visible spectral lines for identification of
the most reactive plasma region in the flow. Results can be helpful in shaping of the gliding discharge reactor ionized
gas region Досліджується питання відповідності форми електродів і потока плазми в реакторі з ковзаючим
розрядом. Ковзаючий розряд підтримувався в повітрі при атмосферному тиску і кімнатній температурі. Було
досліджено три основні конфігурації електродів. Плазма досліджувалася за допомогою видимих спектральних
ліній для виявлення найбільш активних областей у потоці плазми. Результати можуть бути корисні для
створення реактора з ковзаючим розрядом у іонізованій газовій області. Исследуется вопрос соответствия формы электродов и потока плазмы в реакторе со скользящим
разрядом. Скользящий разряд поддерживался в воздухе при атмосферном давлении и комнатной
температуре. Были исследованы три основные конфигурации электродов. Плазма исследовалась с помощью
видимых спектральных линий для выявления наиболее активных областей в потоке плазмы. Результаты могут
быть полезны для создания реактора со скользящим разрядом в ионизованной газовой области.